Musicafatta spirituale. Aquilino Coppini’s contrafacta of Monteverdi’s Fifth Book of Madrigals - Budzińska-Bennett, Agnieszka (Interdisciplinary Studies in Musicology, 2018)
This article focuses on Aquilino Coppini’s contrafacta of Monteverdi madrigals from the Fifth Book, Musica tolta da i Madrigali di Claudio Monteverde, e d’altri autori [...] e fatta spirituale, published in Milan in 1607. Coppini (d. 1629), a Milanese priest, professor of rhetoric at the University of Pavia and man of letters, was Monteverdi’s personal friend and admirer. He was associated with the circle of Cardinal Federico Borromeo (1564-1631), Archbishop of Milan and a great connoisseur of the arts, and his cousin, Cardinal Carlo [Charles] Borromeo (1538-1584), principally responsible for the Tridentine reform of church music, to whom Coppini dedicated the first of his three collections of contrafacta discussed here. Coppini’s efforts in re-texting Monteverdi’s compositions and transforming them into madrigali spirituali were very much welcomed by the mighty Borromeo family, as they allowed the newest stylistic achievements of the seconda prattica to be transferred to church music. Coppini’s contrafacta are of interest for their concentration on madrigals by Monteverdi, as Coppini chose to work on eleven madrigals from Monteverdi’s controversial Fifth Book. His treatment of the poetic text is quite elaborate. First, his Latin contrafacta are creative re-textings in which he reproduces the metric structure and the sound quality of Guarini’s original Italian texts through the careful placement of phonemes, vowels and consonants. Second, he transforms them into madrigali spirituali, always following their original affetti, creating strong associations and often profound intertextual relationships among the original and the new texts, in which he elevates the profane situations from Guarini’s texts to the spiritual level of the Gospel teachings. In this respect, Coppini’s work remains a fascinating contribution to the enduring discussion on the thin line between the sacred and the profane.